The Making of a Gay Muslim Religion, Sexuality and Identity in Malaysia and Britain - Shah, Shanon (Palgrave Studies in Lived Religion and Societal Challenges, 2018)
This book highlights the lived experiences of gay Muslims in Malaysia, where Islam is the majority and official religion, and in Britain, where Muslims form a religious minority. By exploring how they negotiate their religious and sexual identities, Shah challenges the notion that Islam is inherently homophobic and that there is an unbridgeable divide between 'Islam' and the 'West'. Shah also gained access to gay Muslim networks and individuals for his in-depth research in both countries, and the book investigates the different ways that they respond to everyday anti-homosexual or anti-Muslim sentiments. Amid the many challenges they confront, the gay Muslims whom Shah encountered find innovative and meaningful ways to integrate Islam and gay identity into their lives. The Making of a Gay Muslim will appeal to students and scholars with an interest in contemporary Islam, religion, gender and sexuality.